Effect of Knowledge and Locus Of Control on Intellectual Capital and Quality of Financial Reports - Salmiyah Thaha; Irdawati Irdawati; Hariyanti Hariyanti; Leni Saleh; Hardiyono Hardiyono (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study aims to determine the effect of knowledge and locus of control on intellectual capital and its impact on the Quality of Financial Reports at PT. State Electricity Company (PLN) for Wajo, Bone, and Pare-Pare regions. The data in this study were obtained from each manager of PT. PLN (Persero) in Wajo, Bone and Pare-Pare areas. In this study, we used primary data by giving questionnaires/question sheets directly to 36 respondents. The data analysis method used is Structural Equation Model (SEM) analysis using Smart-PLS. The results showed that the knowledge variable had a positive effect on intellectual capital and the quality of accounting information reporting, and locus of control had a negative and significant impact on intellectual capital and the quality of accounting information reporting. The knowledge variable positively and significantly affects the quality of Financial Reports through intellectual capital. In contrast, locus of control significantly negatively affects the quality of Financial Reports through intellectual capital. The results of this study are used as information and input for company leaders in the context of making decisions and policies according to the quality of accounting information reporting. The results of this study can also be used for other researchers and parties who need it as a source of reference and information that can later be used for further research.